PEMANFAATAN GLOBAL POSITIONING SYSTEM (GPS) PADA PRESENSI KARYAWAN BERBASIS SMARTPHONE - Andre Setya Yudhanto; Migunani (STEKOM PRESS, 2020)
The development of technology allows one to obtain other people's spatial position data. One mobile technology that utilizes spatial data as a supported factor is location-based services. The large number of employees at the PT.XYZ causes the presence of a controlled process to be under control, and even tends to be questioned. Because it takes a GPS-based presence system on android that is expected to be a solution of the problems that occur at this time. The system development method used is a six-step R&D method, consisting of: Research and information gathering, Planning, Development of initial product forms, initial field testing, major product revisions, main field testing. The final result is the prototype of the Ganesha Employee Presence System Operations. The test results on the system shows the employee attendance system can run on the android platform. The system only responds to presence based on the position of the employee's coordinates with office coordinates. Besides checking the presence process is also based on devices that have been approved in the system.